PATRIOTIC THEATER: A STUDY OF GHARBI MUSTAFA’S LEYLA, THE KURDISH BRIDE & W.B. YEATS’ CATHLEEN NI HOULIHAN - Kurdi, Diyar; Abdulkarim, Chiad (Humanities Journal of University of Zakho, 2025)
The present study is an attempt to examine the representation of patriotism and nationalism in Irish and Kurdish plays. Specifically, the researcher deals with two dramas one penned by the Kurdish playwright Gharbi Mustafa, and the other by the Irish dramatist William Butler Yeats. Their stage plays, Mustafa’s Leyla, The Kurdish Bride (2010), and Yeats’ Cathleen Ni Houlihan (1902), have been taken into account in order to analyze how the two aforesaid plays are patriotic in nature. For the purpose of achieving the aim of the study, i.e., investigating expressions of national pride and belonging, a careful attention is given to specific symbols, motifs, characterizations, and narratives present in the opted scripts. The analysis of the study signifies that Yeats makes use of an Irish myth-derived figure, namely Cathleen who, in reality, is an incarnation of Ireland, to depict national identity and political conflicts. Meanwhile, Mustafa fictionalizes the true events of a Kurdish martyr, Leyla Qasim, to enlighten the Kurdish case and how the Kurds have been deprived of their privileges for ages. The two dramatic works thematize persecution, foreign oppression, a longing for freedom among other related themes. The paper comes to the conclusion that although these two plays are written over a century apart, yet in tandem they shed light on political oppression, a wish to be free, and national belonging.